Penerapan pengelolaan risiko terintegrasi: Fondasi keberlangsungan perbankan syariah - Nasution, Nurul Fadhilah (Maliki Interdisciplinary Journal, 2024)
This article focuses on the implementation of risk management in Islamic banking. Risk management plays a crucial role in the operations of Islamic banking institutions. Good implementation of risk management can help Islamic banks manage market, credit, liquidity, and operational risk. The purpose of this article is to understand the importance of implementing risk management in ensuring the stability and growth of Islamic financial institutions. The method used in this article is literature study from various sources. The results of this research are that by controlling risks, monitoring them regularly, and maintaining effective risk governance, Islamic banks can grow shareholder value and ensure sustainable business operations in line with Sharia principles.